Anesthethic approach of mucopolysaccharidoses - Marcelino, Margarida; Marote, Luísa; Patuleia, Maria Domingas (Journal of the Portuguese Society of Anesthesiology, 2016)
Mucopolysaccharidoses (MPS) are a group of hereditary disorders caused by a deficiency of glycosaminoglycan (GAG) metabolism enzymes, with subsequent incomplete breakdown of GAG, which accumulate in organs. They are chronic and progressive disorders. Cardiac and respiratory involvements are the principal causes of mortality. Patients with MPS are frequently submitted to surgical procedures. Nowadays, these patients’ increase in life expectancy causes their perioperative management to be a concern for all anaesthetists. Despite breakthroughs in the anaesthetic and surgical approach, perioperative mortality is still high among patients. Preoperative evaluation includes a thorough clinical history and note of prior surgical procedures or anaesthesias. Airway evaluation should include diagnostic imaging to identify odontoid dysplasia or atlantoaxial subluxation. Locoregional techniques should be chosen whenever possible, in order to avoid airway management. However, this may not always be possible due to the patient’s age, comorbidities and surgical procedure. Airway management may be achieved with orotracheal intubation, either by laryngoscopy or fiberoptic techniques, laryngeal mask or tracheostomy. In these patients postoperative management should take place in an Intensive Care Unit.